2008
DOI: 10.1007/s00253-008-1537-8
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of docosahexaenoic acid-rich lipid in thraustochytrid Aurantiochytrium sp. strain T66: effects of N and P starvation and O2 limitation

Abstract: Aurantiochytrium sp. strain T66 was grown in batch bioreactor cultures in a defined glutamate- and glycerol-containing growth medium. Exponentially growing cells had a lipid content of 13% (w/w) of dry weight. A fattening of cells fed excess glycerol occurred in the post-exponential growth phase, after the medium was depleted of N or P. Lipid accumulation was also initiated by O2 limitation (below 1% of saturation). N starvation per se, or in combination with O2 limitation, gave the highest lipid content, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(81 citation statements)
references
References 34 publications
2
77
1
1
Order By: Relevance
“…The DHA content in these species commonly reaches 50 of their total fatty acids 17,22 . In this study, similarly higher DHA contents were also observed in T. aureum and T. roseum, in which they were much higher than those in all of the other strains T. striatum and Schizochytrium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The DHA content in these species commonly reaches 50 of their total fatty acids 17,22 . In this study, similarly higher DHA contents were also observed in T. aureum and T. roseum, in which they were much higher than those in all of the other strains T. striatum and Schizochytrium spp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Duan et al (2012) reported that Chlorella vulgaris experienced a 21.1% increase of lipid yield when exposed to salt pressure. Biosynthesis of lipids is also induced by other physical environmental stresses, such as low oxygen in the microalga Aurantiochytrium sp., and dehydration in the green alga Chlorella kessleri (Jakobsen et al, 2008; Shiratake et al, 2013). …”
Section: Lipid Accumulation In Oleaginous Microorganisms Under Differmentioning
confidence: 99%
“…Very recently, it has also been suggested as a potential feedstock for biodiesel industry (Adamczak et al, 2009;Easterling et al, 2009;Li et al, 2008;Vicente et al, 2010), because microbial lipid can be produced using various cheap feedstocks, especially renewable biomaterials such as lignocelluloses. Early studies suggested that oleaginous microorganisms should be cultivated for lipid accumulation in the media with excess carbon sources and one particular limiting element such as nitrogen, phosphorus, zinc, iron or magnesium (Gill et al, 1977;Jakobsen et al, 2008). Thus, when the limiting nutrient was exhausted, cell growth was repressed and the remaining carbon source was converted to storage lipid.…”
Section: Introductionmentioning
confidence: 99%